Incidence of Chronic Opioid Use in Previously Opioid-Naïve Patients Receiving Opioids for Analgesia in the Intensive Care Unit - Adil, Mohammad Q. (Fed Pract, 2020)
OBJECTIVE: Inappropriate prescribing of opioids has contributed to misuse and a rise in accidental deaths. The purpose of this study was to determine the incidence of chronic opioid use in previously opioid-naïve patients who received opioids for analgesia while in the intensive care unit (ICU) and to identify potential risk factors in patients that transition to chronic opioid use. METHODS: A retrospective analysis included patients admitted to the medical, surgical, or cardiovascular ICU at the Michael E. DeBakey VA Medical Center in Houston, Texas, between August 2017 and December 2017. Patients were screened to confirm opioid-naïve status prior to admission, defined as ≤ 30 days of opioid prescription use in the prior 12 months. Patients were included if they received a continuous opioid infusion for ≥ 12 consecutive hours. Prescription fill data from the health record were examined at 3, 6, and 12 months postdischarge to determine whether patients were receiving chronic opioid treatment. RESULTS: Records of 330 patients were reviewed and 118 patients met the inclusion criteria. All patients received fentanyl infusion, for a median time of 35 hours (interquartile range 18.8–64.7 hours). Ninety (76.3%) patients were receiving opioids postdischarge at 3 months, 23 (19.5%) at 6 months, and 9 (7.6%) at 12 months. At 3 months, ICU type (odds ratio [OR], 3.9; 95% CI 1.73–8.75; P < .001) and being a surgical patient (OR, 7.8; 95% CI 3.26–18.56; P < .001) were risk factors for chronic opioid use. No specific risk factors were found to increase the risk of chronic opioid use at 6 and 12 months. CONCLUSIONS: The incidence of chronic opioid use decreased at 6 and 12 months compared with that of 3 months postdischarge. ICU type and hospital admission related to surgery were not associated with increased opioid use at 3 months.